Antitumor activity of methoxylated flavonoids separated from Achillea fragrantissima extract in Ehrlich's ascites carcinoma model in mice - Basma M. Awad; Mohammad M. Abd-Alhaseeb; Eman S. Habib; Amany K. Ibrahim; Safwat A. Ahmed (Shahrekord University of Medical Sciences, 2020)
Introduction: Achillea fragrantissima extract has been used in folk medicine as an anticancer. The present study describes the antitumor activities of the extract and the flavonoid compounds and attempts to explain the mechanisms underlying these activities. Methods: The whole plant of A. fragrantissima was collected and ground to produce a fine powder which subjected to the maceration process. Step gradient elution was used using silica gel vacuum liquid chromatography (VLC). The fractions were compared by thin layer chromatography (TLC) and concentrated. Final purification was performed using Sephadex LH-20 to give three compounds cirsiliol, chrysosplenol D and cirsimaritin from F4 and one compound, eupatilin-7-methyl ether from F6. In this study, Ehrlich's ascites carcinoma (EAC) model was used as the model of cancer. Results: Achillea fragrantissima extract and its isolated methoxylated flavonoids significantly reduced the weight of tumor discs compared to EAC-control group. In addition, cirsimaritin and eupatilin 7-methyl ether treatments produced a dose-dependent reduction in tumor weight. Serum tumor necrosis factor-alpha (TNF-ɑ) level showed that A. fragrantissima extract and its isolated methoxylated flavonoid compounds significantly reduced its serum level compared to the EAC-control group. Furthermore, A. fragrantissima extract and the flavonoids significantly increased the Total antioxidant capacity (TAC) compared to EAC-control. A. fragrantissima extract and its isolated methoxylated flavonoids produced a better differentiation of tumor cells, with reduced nuclear pleomorphism and better formed tubular structures especially with high dose indicating the induction of apoptotic mechanism. Conclusion: Achillea fragrantissima extract and its isolated methoxylated flavonoids exhibit antitumor activities that may be attributed to the antioxidant properties and the induction of the apoptotic process.